Magic Graphical Symbols as Subject of Scientific Investigations - I. I. Miachikova (Наука и техника)
The paper contains a short review of scientific insights about the essence of graphical symbols in the period of occult insight domination in science. It is shown that all the works of this period in respect of the investigated problem belong to the following three directions - religious, alchemical and nature-philosophical. Analysis of these works proves that rather high level of knowledge about esoteric of graphical symbols was achieved at that time.